Development of Electronic Module with Augmented Reality on Pyramid for VIII Grade - Evalia Nuryana; Atik Wintarti (MATHEdunesa, 2022)
In order to create a joyful learning environment, especially during a pandemic that requires learning to be carried out online, an innovation is needed such as the use of interactive learning media for mutual learning which can be accessed online. Electronic modules with Augmented Reality are packaged in the form of learning media that can be used independently everytime and everywhere. This study aims to develop an electronic module with android-based Augmented Reality named "AR LIMAS" as a media to improve students' abilities on pyramid geometry problem. The selection of pyramid material in the electronic module was based on several previous studies regarding the misconceptions experienced by students on pyramid. The development of this electronic module used the ADDIE research method by taking into account the scores ​​of validity, practicality, and effectiveness for the creation of good learning media. This electronic module was tested on 3 students of VII grade who have low, medium, and high mathematical ability. The categorization of students' mathematical ability was based on the final examination scores in the previous semester. Based on the assessment of experts, this electronic module was declared to have a good category with a validity percentage of 86.59%. Then the results of the questionnaire using the electronic module obtained a practicality percentage value of 98.35% with a very good category. The results of pretest with an average score of 15 increased in posttest with an average score of 82.5, so the module was considered effective in improving students' understanding on pyramid. Keywords: electronic module, android, augmented reality, pyramid, development.